MORPHOLOGY AND MORPHOMETRIC INDICES OF THE OVARY IN WHITE LABORATORY RATS IN POSTNATAL ONTOGENESIS - Dilorom Adilbekova; Sevara Kuranbaeva; Malokhat Nazarova; Mubina Davranova (Central Asian Journal of Medicine, 2025)
This study investigates the morphological and morphometric changes in the ovaries of white laboratory rats during postnatal ontogenesis. We analyze the developmental stages of the ovary from neonatal to mature adulthood, examining structural transformations and key morphometric indices such as ovarian volume, follicular count, and corpus luteum size. The results provide insight into ovarian growth patterns, folliculogenesis, and reproductive maturation, contributing to a deeper understanding of reproductive physiology in laboratory rodents.